Farmers for a sustainable future - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1995)
In June 1992, at the Earth Summit in Rio de Janeiro, farmers were recognized as one of the major groups whose activities were most closely linked to environmental and developmental issues. Two years later, the 80 national farmers' organizations...